RE-STUDY ON CAM GROOVE PROFILE AND KINEMATICS CHARACTERISTICS BASED ON ROTATING SLEEVE DISTRIBUTING-FLOW SYSTEM - CHENG QianChang; ZHANG HongXin; ZHAO QingHai; ZHANG YanJun; JIANG XiaoTian (Jixie qiangdu)
Rotating sleeve distributing-flow system is a new-type distributing-flow system,overcoming the shortcomings of traditional valve-type flow distribution systems such as large volume,loose structure,and low volumetric efficiency. The cam groove profile of the rotating sleeve directly affects the kinematics characteristics of rotating sleeve distributing-flow system. In this paper,by analyzing the self-locking characteristics of the sinusoidal cam groove profile,four new types of cam groove profiles are proposed,the kinematics analysis of rotating sleeve and drive pins under the four cam groove is performed. The results showed that: the amplitude of the angular velocity and angular acceleration of the line cam groove profile rotating sleeve is the smallest,which is 203. 1 rad/s and 4. 961 × 10~4 rad/s~2,respectively,and there are two impacts in one cycle; The radial speed and acceleration of drive pin under line cam groove profile is the smallest,which is -0. 387 m/s and 115. 0 m/s~2,respectively,and there is no impact during cycles. So,the line cam groove profile is the best choice.